Kualitas MP-ASI dan hubungan dengan status gizi pada anak penderita ISPA di Bengkulu - Melita Sari; Demsa Simbolon; Ahmad Rizal; Desri Suryani; Jumiyati Jumiyati (Jurnal SAGO Gizi dan Kesehatan, 2024)
Background: The 2022 Indonesian Nutrition Status Survey results show that the stunting rate reaches 21.6%, wasting 7.7%, and underweight 17.7%. Malnutrition problems in toddlers, especially those suffering from Acute Respiratory Infection (ARI), are often exacerbated by the provision of Complementary Feeding that does not meet nutritional standards. Therefore, greater attention to complementary feeding quality is essential to improving children's nutritional status and reducing the risk of ARI complications.Objective: To identify the relationship between the quality of complementary breastfeeding and nutritional conditions, such as underweight, wasting, and stunting, in children under two years of age suffering from ARI, as an urgent effort to address malnutrition problems and improve children's health in vulnerable communities.Methods: This study used a cross-sectional design with a target of toddlers aged 6-24 months who suffered from ARI, with a sample of 96 children. Data on complementary breastfeeding was collected through interviews using questionnaires, as well as weight measurements with digital scales and height with a lenghtboard. Statistical analysis using the Chi-square test.Results: Nutritional problems in two-year-old children with ISPA were found to be 44.8% underweight, 60.4% wasting, and 36.5% stunting. Complementary Feeding quality that did not meet the recommendations was significantly associated with the incidence of being underweight (p-value 0.035; OR 2.488), and wasting (p-value <0.0001; OR 6.657), but was not significantly associated with the incidence of stunting (p-value 0.95; OR 0.973).Conclusion: The quality of Complementary Feeding that does not meet nutritional standards in children with ARI is significantly related to the incidence of underweight and wasting.